Profitability and Feasibility of Onion Farming in The Lower Plains - Cordanis, Astried Priscilla; Bana, Maryance Vivi Murnia; Keraru, Ester Nurani; Ngoni, Maria Salestina (JURNAL AGRIBISAINS, 2024)
Due to the increasing demand for shallots from households, companies, and industry, the per capita consumption rate of shallots is expected to increase by 8.21% in 2021, making shallots a high-value horticulture product with great business opportunities. Reok District is a subdistrict that is suited for cultivating shallots because it is situated in a lowland region at a height of 12 meters above sea level. 50% less land was cultivated than the previous year. Reok Sub-District is a center for producing shallots in Manggarai Regency, which is a basis for considering a selection of research locations. The decrease in planting area will have an impact on shallot production in Manggarai Regency. 50 shallot farmers, who were specifically selected as the samples, were added. With the assist of the income equation and R/C ratio analysis, this study seeks to ascertain the profitability and viability of shallot farming in Reok sub-district. Based on the analysis’s findings, it was determined that shallot farming in Reok sub-district generated an average revenue of Rp. Rp32,304,679.04 with an average of 0.51ha, and the R/C ratio was 1.85, which indicated that the sub-district’s shallot farming was deemed to be feasible. This research examines BEP unit and rupiah BEP as material for consideration in the implementation of agricultural activities in the next period in addition to revenue and business viability analysis. where the rupiah BEP is IDR 4,441.45/kg and the unit BEP is 1996.095 kg.